Humungous II all ages no-alcohol show : [featuring] Thrombus, Chevelles, Kryptonics, Yummy Fur : plus winner of Revue Highschool Band Comp. ([Melbourne : s.n., 1992)
Advertisement for Humungous II at the Beat Room, The Young Melbourne, 22 December. Features images of skulls on a pale yellow (card) background.
Caption title.
"Triple J, Revue presents"--at head of caption title.
Digital master available
Keywords: Rock music -- Australia -- Posters; Rock concerts -- Victoria -- Posters; Popular music -- Australia -- Posters; Posters, Australian; Australia -- Posters; Australian